Reducing Health Inequalities in Aging Through Policy Frameworks and Interventions - MacGuire, Frances A. S. (Frontiers in Public Health, 2020)
Lifepath, a European Commission Horizon 2020 programme of research, adopted a life course 17 approach to understanding the impacts of socioeconomic differences on healthy ageing and 18 considered the relative importance of lifetime effects by comparing studies on childhood and 19 adult risks. A key component of the programme was the identification of policy relevant results 20 and messages. 21 Longitudinal European cohorts of over 1.7 million individuals from 48 independent cohort 22 studies were harmonised and followed for the key outcomes of mortality and functional 23 decline. Biological markers, allostatic load and DNA methylation were also examined. 26 It is well recognised that socioeconomic position affects behaviours such as smoking, high 27 alcohol consumption, low physical activity, diabetes or a diet low in fruit and vegetables. 28 Lifepath indicated that socioeconomic status is an independent risk factor for death and disease 29 and that it also helps drive the uptake of these well recognised risk behaviours. 30 The evidence from Lifepath points to a suite of possible policies, some universal, some 31 targeted but it was not possible to assess specific interventions, other than conditional cash 32 transfers. 33 34 Nevertheless it was clear that the timing of interventions is important as the consequences of 35 early interventions may span the whole life course. This has important implications for 36 policy making, since appropriate policies can reverse the embodiment of socioeconomic 37 disadvantage resulting in healthier ageing. Applying principles of proportional universalism 38 should be considered.